Sodobna dramatika in vprašanje dediščine neoavantgarde šestdesetih in sedemdesetih let - Troha, Gašper (Amfiteater (Ljubljana), 2023)
o some extent, contemporary drama is the heir of the neo-avant-garde of the late 1960s and 1970s. This time was that of the so-called performative turn, which pulled theatre away from representation and towards presentation. The subsequent development can be designated by various labels, such as postdramatic theatre, the aesthetics of the performative and, in the case of dramatic texts, the no longer dramatic theatre text, “In-Yer-Face” theatre, etc. In Slovenia, a decisive turn from text to event took place towards the end of the 1960s. During this time, the first happenings and performance art pieces were taking place. In reviewing the performance Pupilija, papa Pupilo pa Pupilčki (Pupillja, Papa Pupilo and the Pupilceks), Veno Taufer went as far as to declare the death of literary theatre. At first glance, it would thus appear that contemporary playwriting is merely repeating earlier patterns. While contemporary playwriting may more radically formulate linguistic and aesthetic games, it deconstructs the dramatic form and thus radicalises the premises of the neo-avant-gardes; in the last two decades, we have been talking about a return to dramatic, post-postdramatic and dramatic drama, etc. Through a comparative analysis of two of the more radical texts from Blaž Lukan’s anthology Generator:: za proizvodnjo poljubnega števila dramskih kompleksov ( The Generator:: for Manufacturing Any Number of Drama Complexes), namely Dušan Jovanović’s Sinopsis za happening Hlapci ( Synopsis for The Happening of Lackeys) and Rastko Močnik’s Generator, ki iz določenih enot in po preprostih pravilih proizvaja poljubno število dramskih kompleksov ( A Generator that Produces Any Number of Drama Complexes from Given Units and According to Simple Rules) as well as Simona Semenič’s mi, evropski mrliči (we, the european corpses) and Varja Hrvatin’s Vse se je začelo z golažem iz zajčkov ( It All Started with the Bunny Rabbit Goulash), the paper shows that the neo-avant-garde is more about the question of theatrical performances and the form of the dramatic text, while contemporary drama is more about the search for authenticity and dramatic effects.
Keywords: Dušan Jovanović; Rastko Močnik; Simona Semenič; Slovenian drama; Slovenian experimental theatre; slovenska dramatika; slovensko eksperimentalno gledališče; Varja Hrvatin